Controlling The Consistency Of Self-Compacting Concrete - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Self-Compacting Concrete or SCC is defined as concrete that has an ability to compact by means of its own weight and without the need for vibrating compaction. This kind of concrete has been introduced since more than 10 years ago and was applied mostly for precast concrete. Currently Self-Compacting Concrete is widely used for big projects including for underwater concrete. In the fresh condition SCC must have a very high consistency and has an ability to flow. This paper discuses the application of Sika ViscoCrete-5 to control the consistency of SCC. In the experiment Sika ViscoCrete-5 admixture and silica fume were used in the mix in addition to water, cement, and aggregate, to achieve the requirements for SCC. Two water-cement ratios of 0.40 and 0.45 were applied with variation of Sika ViscoCrete-5 of 0.3%, 0.6%, 0.8%, 1.0% and 1.3% of binder weight. Three methods of measuring concrete consistency were used, they were slump test, flow table test, and U type test. From the test results it can be concluded that the Sika ViscoCrete-5 should be at least 0.70% for water-cement ratio of 0.45 and 0.80% for water-cement ratio of 0.40 to achieve the requirement of SCC. It is also found that the application of Sika ViscoCrete-5 increases significantly the SCC consistency and compressive strength. However, it is worth to note that as the concrete becomes SCC compaction process shall be omitted to avoid excessive bleeding that tends to reduce the compressive strength.